Penilaian Kerawanan Pohon Tumbang di Sepanjang Jalan Arteri Taman Hutan Raya Bukit Soeharto Menggunakan Google Street View - Ali Suhardiman; Frans Milan; Yosep Ruslim; Ariyanto Ariyanto; Hari Siswanto (Faculty of Forestry Universitas Gadjah Mada, 2024)
The incidence of fallen trees along the roadside was widespread across various locations in Indonesia, particularly in areas where trees naturally thrive. Therefore, this research aimed to explore Google Street View (GSV) to obtain information regarding the potential of fallen trees. A novel approach was proposed using panoramic photos available in GSV data from May 2021 and then subjected to testing along Balikpapan–Samarinda Arterial Road, covering a distance of 33 kilometers (Km), which traversed Bukit Soeharto Grand Forest Park (BSGFP). Leaning trees, trees with imbalanced canopy proportion, dying trees, and trees in rough topography became the criteria specified from GSV photos to determine potentially fallen trees. The results showed that 224 trees along Arterial Road met those criteria, translating to approximately 6.79 trees per kilometer of Arterial Road. The analysis revealed that an imbalance canopy proportion was the primary cause of fallen trees, supported by investigations and comparisons with the corresponding GSV photos before the collapse. The Arterial Road Balikpapan-Samarinda poses moderate fallen tree vulnerability, scoring between 25% and 50%.